The ecclesiastical agents in dispute: Integration, methods and new study perspectives, 16th to 20th centuries - Abadía Quintero, Carolina (2021)
At the beginning of 2019, I received a cordial invitation from the Allpanchis editorial team to coordinate a dossier dedicated to the study of the American clergy. In defining this academic exercise, I determined that it was vital to make visible the ecclesiastical agents and their sociopolitical intermediaries, as well as the historical roles they fulfilled at different times in American history. To achieve this goal, it was vital not only to limit ourselves to a specific spatiality or temporality —the viceroyalty—, but also to consider the articulation of historical periods based on clerical agency. This is how the dossier that I have the honor to present exhibits research on the study of the American clergy in a long-term perspective that goes from the 16th century to the dawn of the 20th century, and that demonstrates the agency, accommodation, mediation , the links and the leading role of the clergy in America.